2005
DOI: 10.1017/s1537592705050449
|View full text |Cite
|
Sign up to set email alerts
|

New Destinations and Immigrant Incorporation

Abstract: Does the academic literature on U.S. immigration adequately capture the experiences of immigrants outside their traditional areas of concentration? This article reviews the three major fields of research in immigrant incorporation-economic, sociocultural, and political. It emphasizes the two most prominent conceptual frameworks in each: the human capital frame and the more recent sociological frame, which highlights "modes of incorporation" and "contexts of reception." Although research in immigrants' politica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 41 publications
0
74
1
Order By: Relevance
“…Adequate employment is a route to immigrants' economic assimilation and social mobility (Marrow 2005). As their time in the U.S., work experience, and English proficiency increase, immigrants' earnings and occupational attainment tend to increase as well (Boyd 1993;Collins 1983).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate employment is a route to immigrants' economic assimilation and social mobility (Marrow 2005). As their time in the U.S., work experience, and English proficiency increase, immigrants' earnings and occupational attainment tend to increase as well (Boyd 1993;Collins 1983).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Active representation of immigrant interests may require a sufficient level of passive representation, salience of immigrant status in the policy context, and bureaucratic discretion (Keiser et al 2002;Sowa and Selden 2003). This suggests that passive representation is particularly important in occupations that have discretion to Immigrant teachers may be more accommodating of immigrant children and children of immigrant parents (Marrow 2005(Marrow , 2009). Immigrant police officers might have better understanding of the needs of immigrant communities (Lewis and Ramakrishnan 2007) .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Immigrant nonprofit organizations also take part in immigrant political incorporation, characterized both by participation in electoral politics (De Sipio 1996Gerstle and Mollenkopf 2001) and by the wide range of non-electoral activities -from volunteering, to petition-signing, to attendance at rallies, marches, and demonstrations -promoted by these organizations (Jones-Correa 1998a, 1998bPutnam 2001;Verba et al 1995). These non-electoral activities should be included when discussing immigrant political incorporation (Bloemraad 2006b;Cordero-Guzmán et al 2008;Marrow 2005;Ramakrishnan and Espenshade 2005), given the inability of many undocumented immigrants to pursue American citizenship and, as a result, to exercise voting privileges. Immigrant political incorporation is generated largely by the efforts of nonprofit organizations as opposed to political parties (Andersen and Cohen 2005;CorderoGuzmán et al 2008;De Graauw 2008;Jones-Correa 2005;Pantoja et al 2008), due to the initial contact immigrants make in their neighborhood with nonprofits, ranging from congregations, to community centers, to ethnic-based organizations (Jones-Correa, 2005).…”
Section: Immigrant Nonprofit Organizations As Political Actorsmentioning
confidence: 99%
“…Additionally, social movements are more likely to flourish where there is higher receptivity of the cause by both residents and the local political culture (Marrow 2005). Furthermore, social movements are affected by political and economic cycles, which quickly serve to heighten popular support or opposition around the issue.…”
Section: Measuring Movement Effectivenessmentioning
confidence: 99%
“…Scholars of immigrant incorporation have shown that CBOs can facilitate the social, economic, and civic incorporation of immigrant groups (for example see Campos 2014;DeSipio 2001;Marrow 2005;Ramakrishnan and Bloemraad 2008;Wong 2006). Given the important roles that they play in immigrant communities, we encourage CBOs to use their platforms as trusted messengers to not only convey information about potential paths to lawful immigration status beyond DACA-and that such paths may exist even in the absence of comprehensive immigration reform legislation or eligibility for administrative relief-but also to direct unauthorized immigrants to competent immigration legal service providers.…”
Section: Recommendationsmentioning
confidence: 99%